Glass ceramic suitable for deep processing, glass product and deep processing method
By adjusting the crystal phase composition and deep processing technology of microcrystalline glass, the problem of difficulty in the deep processing of microcrystalline glass is solved, the effect of reducing the glass softening temperature and controlling the crystal size is achieved, and the processing performance and performance indicators of microcrystalline glass are improved.
Patent Information
- Application Number
- CN202411170255.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-03-04
AI Technical Summary
The existing microcrystalline glass is difficult during deep processing, and the high strength makes it difficult to follow-up processing.
By adjusting the crystal phase composition of the microcrystalline glass, including lithospar, lithium silicate and lithium dissilicate, the crystallinity is controlled to be less than or equal to 75%. The total content of lithospar and lithium dissilicate accounts for more than 65% of the total crystal content, and preheating, thermal bending molding and cooling are carried out during deep processing.
It effectively reduces the softening temperature of the glass, simplifies the deep processing process, and controls the total crystal content and size, improving the mechanical and optical properties of the microcrystalline glass.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to the field of glass technology. Specifically, the present application discloses a microcrystalline glass suitable for deep processing, a glass product and a deep processing method. Background Art
[0002] Compared with traditional aluminosilicate glass, glass-ceramics has a higher Young's modulus to resist impact deformation, and has a higher fracture toughness to inhibit crack propagation. In addition, glass-ceramics has a natural and soft texture, and can obtain rich and colorful colors through composition and process control. Because glass-ceramics contains a crystalline phase, its hardness and wear resistance are higher than ordinary glass, and its softening temperature is also higher than ordinary glass, which increases the difficulty of subsequent deep processing such as grinding, pressing, and hot bending.
[0003] It is worth noting that the techniques described in this section are not necessarily techniques that have been previously conceived or employed. Unless otherwise indicated, it should not be assumed that any technique described in this section is considered to be prior art simply because it is included in this section. Similarly, unless otherwise indicated, the issues mentioned in this section should not be considered to have been recognized in any prior art. Summary of the invention
[0004] The present application provides a microcrystalline glass, a glass product and a deep processing method suitable for deep processing, aiming to solve at least one of the problems in the related art to a certain extent.
[0005] In a first aspect, the present application provides a microcrystalline glass suitable for deep processing, wherein the crystalline phases of the microcrystalline glass include petalite, lithium disilicate and lithium silicate, and the degree of crystallinity is less than or equal to 75%; the content of the petalite accounts for 30-60% of the total crystal content, the content of the lithium disilicate accounts for 16-38% of the total crystal content, the content of the lithium silicate accounts for 10-35% of the total crystal content, and the combined content of the petalite and the lithium disilicate accounts for more than 65% of the total crystal content.
[0006] Optionally, the crystal phase of the glass-ceramics further includes at least one of lithium phosphate and β-spodumene.
[0007] Optionally, the crystallinity of the glass-ceramics is 58-75%.
[0008] Optionally, the content of petalite accounts for 40-60% of the total crystal content, and / or the content of lithium disilicate accounts for 16-30% of the total crystal content, and / or the content of lithium silicate accounts for 15-35% of the total crystal content.
[0009] Optionally, the components of the microcrystalline glass include, by weight percentage: SiO2: 70-75%, B2O3: 0.35-1.2%, Al2O3: 7.5-9.5%, Na2O: 0.5-1.5%, Li2O: 9.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
[0010] Optionally, the components of the microcrystalline glass, in terms of weight percentage, meet the following conditions: Li2O / (SiO2+Al2O3): 0.1 to 0.2.
[0011] Optionally, the crystallization temperature of the glass-ceramics is 655-700°C.
[0012] Optionally, the microcrystalline glass meets at least one of the following indicators: glass transition temperature less than or equal to 650°C, glass softening temperature less than or equal to 720°C, Vickers hardness less than or equal to 710kgf / mm 2 , the average crystal particle size is less than or equal to 30nm, the average transmittance of visible light with a wavelength of 380 to 780nm is greater than or equal to 80% when the thickness is 0.6mm, the |B| value when the thickness is 0.6mm is 0.6 to 1, and the haze when the thickness is 0.6mm is 0.15 to 0.25%.
[0013] The second aspect of the present application provides a deep-processed microcrystalline glass product, which is obtained by subjecting the microcrystalline glass described in the first aspect of the present application to heat processing and cold processing.
[0014] The third aspect of the present application provides a deep processing method for microcrystalline glass, comprising: sequentially performing preheating treatment, hot bending treatment and cooling treatment on the microcrystalline glass described in the first aspect of the present application to obtain a deep-processed microcrystalline glass product.
[0015] As can be seen from the above, according to the microcrystalline glass, glass products and deep processing methods suitable for deep processing provided by the present application, the crystal phase of the microcrystalline glass includes petalite, lithium disilicate and lithium silicate, and the crystallinity is less than or equal to 75%; the content of petalite accounts for 30-60% of the total crystal content, the content of lithium disilicate accounts for 16-38% of the total crystal content, the content of lithium silicate accounts for 10-35% of the total crystal content, and the total content of petalite and lithium disilicate accounts for more than 65% of the total crystal content. Through the implementation of this application, the strength of the microcrystalline glass can be guaranteed within the set crystallinity range while effectively reducing the softening temperature of the glass, so that the difficulty of subsequent deep processing is reduced. In addition, in the subsequent deep processing process, the lithium silicate of the microcrystalline glass can continue to react and convert into lithium disilicate, which can effectively control the total crystal content and crystal size.
[0016] It should be understood that the content described in this section is not intended to identify the key or important features of the present application, nor is it intended to limit the scope of the present application. The further effects of the above non-conventional optional methods will be described below in conjunction with specific implementations. DETAILED DESCRIPTION
[0017] In order to make the purpose, features, and advantages of the invention of this application more obvious and easy to understand, the technical solutions in the embodiments of this application will be clearly and completely described below in combination with the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.
[0018] In the description of the embodiments of the present application, the term "plurality" means two or more than two, unless otherwise clearly and specifically defined; the term "comprising" indicates the presence of the described features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections; the term "and / or" describes the association relationship of the associated objects, indicating that three relationships may exist. For example, A and / or B may include the three situations of A existing alone, A and B existing at the same time, and B existing alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship; the term "approximately" means that the content, size, parameter, etc. are not and do not need to be precise. If necessary, they can be approximate or higher or lower. Generally speaking, regardless of whether there is an explicit description, the content, size, parameter, etc. should be "approximately" or "approximately"; the terms "preferably" and "optional" are not used to limit the scope of the present application, nor do they mean that certain technical features are critical or indispensable to the implementation methods of the present application, but should be understood as only indicating specific aspects of the embodiments of the present application.
[0019] Unless otherwise specified in specific circumstances, the numerical ranges recorded in the examples of the present application are intended to include the endpoints of the numerical range and all integers and fractions within the range. When describing a certain amount, solubility or other parameter in the form of a preferred range or a preferred value, it should be understood that it is equivalent to revealing any range by combining any preferred range with a preferred range, a preferred value with a preferred value, or a preferred range with a preferred value, without considering whether this combination is specifically explained in the examples.
[0020] Unless otherwise specified in specific circumstances, the content of components recorded in the examples of the present application is expressed in weight percentage (wt%).
[0021] As the use scenarios of microcrystalline glass become more and more extensive, users have begun to put forward more diversified demands on the form and performance of microcrystalline glass, and thus the post-processing of microcrystalline glass (such as hot processing, cold processing, etc.) has become more normalized. The microcrystalline glass provided in the current related technologies usually only considers the need to ensure a high strength to improve the drop resistance and scratch resistance of the microcrystalline glass, but ignores the problem that the high strength of microcrystalline glass will lead to greater difficulty in post-processing.
[0022] In order to at least to some extent solve the problem that the subsequent deep processing of the micro-ceramic glass provided in the related art is relatively difficult, an embodiment of the present application provides a micro-ceramic glass suitable for deep processing, wherein the micro-ceramic glass is a solid material including a crystal phase and a residual glass phase, wherein the crystal phase includes petalite (LiAlSi4O 10 ), lithium disilicate (Li2Si2O5) and lithium silicate (Li2SiO3), with a crystallinity of less than or equal to 75%; the content of petalite accounts for 30-60% of the total crystal content, for example 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%; the content of lithium disilicate accounts for 16-38% of the total crystal content, for example 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%; the content of lithium silicate accounts for 10-35% of the total crystal content, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 35%; the total content of petalite and lithium disilicate accounts for more than 65% of the total crystal content.
[0023] In practical applications, the glass raw materials are first mixed evenly and then melted to obtain substrate glass, and then the substrate glass is subjected to nucleation and crystallization treatment to obtain microcrystalline glass. After the nucleation treatment, the glass can grow a crystal nucleus, and after the crystallization treatment, a specific crystal can be grown on the basis of the crystal nucleus. In this embodiment, preferably, the nucleation treatment temperature is 530-580°C, the nucleation treatment time is 120-300 minutes, the crystallization treatment temperature is 650-700°C, and the crystallization treatment time is 30-90 minutes.
[0024] In an optional implementation manner of this embodiment, the crystal phase of the microcrystalline glass further includes at least one of lithium phosphate and β-spodumene.
[0025] That is, the main crystalline phase of the crystallized glass-ceramics in this embodiment includes petalite, lithium disilicate and lithium silicate, and the secondary crystalline phase may include at least one of lithium phosphate and β-spodumene.
[0026] In an optional implementation manner of this embodiment, the content of petalite accounts for 40-60% of the total crystal content, and / or the content of lithium disilicate accounts for 16-30% of the total crystal content, and / or the content of lithium silicate accounts for 15-35% of the total crystal content.
[0027] In practical applications, the crystal content, crystal size, etc. of the microcrystalline glass will change due to the reheating during the subsequent heat treatment, which can easily make the mechanical properties and optical properties of the final deep-processed microcrystalline glass products not meet expectations. Specifically in the embodiment of the present application, since lithium silicate can react with SiO2 in the glass during the heating process to be converted into lithium disilicate, for the application scenario where the microcrystalline glass needs to be heat-processed later, the lithium silicate crystal phase of the microcrystalline glass in the embodiment of the present application will melt during the heating process, and transform into the lithium disilicate crystal phase, so that the total crystal content and crystal size in the microcrystalline glass after deep processing are effectively controlled, and considering that too high a lithium silicate content will cause the haze of the microcrystalline glass to increase, the embodiment of the present application limits its content to an upper limit of 35%.
[0028] It is worth mentioning that the embodiment of the present application optimizes the formula of microcrystalline glass. In the optional implementation mode of this embodiment, the components of the microcrystalline glass, measured in weight percentage, include: SiO2: 70~75%, B2O3: 0.35~1.2%, Al2O3: 7.5~9.5%, Na2O: 0.5~1.5%, Li2O: 9.5~12%, P2O5: 1.8~2.6%, ZrO2: 3.5~5.5%.
[0029] SiO2 is the basic component of the glass composition provided in the present application, and is a network structure former of glass and glass-ceramics, and forms lithium silicate and lithium disilicate after crystallization. It should be noted that if the content of SiO2 is low, then the crystals formed in the glass-ceramics will become less and the crystals will become coarser, affecting the haze, drop ball test height and other properties of the glass-ceramics and glass-ceramics products. Therefore, the lower limit of the SiO2 content is set to 70%; in addition, if the SiO2 content is higher than a certain level, the glass melting temperature will be high, the material will be difficult to form, and it will not be easy to form, affecting the consistency of the glass. Therefore, the upper limit of the SiO2 content is set to 75%. In some embodiments, the glass composition may contain about 70%, 71%, 72%, 73%, 74%, and 75% SiO2. Preferably, the content of SiO2 is 70 to 72%.
[0030] B2O3 is the basic component of the glass composition provided in the present application, which can reduce the melting temperature of the glass, and at the same time remain in the glass phase after crystallization, ensuring the structural stability of the glass phase and improving the chemical stability of the microcrystalline glass, but too high B2O3 will increase the volatilization during the glass melting process and increase the difficulty of glass homogenization. Based on this, the lower limit of the B2O3 content is set to 0.35% and the upper limit is set to 1.2%. In some embodiments, the glass composition may contain about 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2% B2O3. Preferably, the content of B2O3 is 0.5-1.2%.
[0031] Al2O3 can be a component that forms a glass network structure, or it can be a cationic network exosome that balances charge. In the present application, all Al2O3 enters the glass network structure, improves the chemical stability of the glass, improves the mechanical properties of the glass, and increases the depth of the ion exchange layer and surface stress of the microcrystalline glass product. On the one hand, if its content is lower than a certain level, it will lead to poor results. Therefore, the lower limit of the mass percentage content of Al2O3 is 7.5%; on the other hand, if the content of Al2O3 is higher than a certain level, the melting and devitrification resistance of the glass will be reduced, and the crystals will easily increase during crystallization, reducing the strength of the microcrystalline glass and microcrystalline glass products. Therefore, the upper limit of the Al2O3 content is 9.5%. In some embodiments, the glass composition may contain about 7.5%, 8%, 8.5%, 9%, and 9.5% Al2O3. Preferably, the content of Al2O3 is 8 to 9.5%.
[0032] Li2O is an essential component that becomes a crystalline phase after crystallization, helps to form lithium-containing crystalline phases such as lithium disilicate, petalite, and lithium silicate, and is also an essential component for chemical strengthening. However, if its content is lower than a certain level, the effect is not good. Therefore, the lower limit of the Li2O content is 9.5%. On the other hand, if too much Li2O is contained, it is easy to reduce the chemical stability of the glass and increase the product cost. Therefore, the upper limit of the Li2O content is preferably 12%. In some embodiments, the glass composition may contain about 9.5%, 10%, 10.5%, 11%, 11.5%, and 12% Li2O. Preferably, the content of Li2O is 10.5-12%.
[0033] Na2O helps to lower the glass transition temperature, crystallization temperature and inhibit the precipitation of unexpected impurities. It exists as other alkali metal oxides besides Li2O, and its lower limit is set to 0.5%. If the introduced Na2O content is too high, the thermal expansion coefficient of the glass will increase and the thermal stability of the glass will be reduced, so the upper limit of its content is set to 1.5%. In some embodiments, the glass composition may include about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% Na2O. Preferably, the content of Na2O is 1 to 1.5%.
[0034] P2O5 helps to improve the low-temperature melting property of glass, can phase separate in the glass to form crystal nuclei, and improve the thermal expansion stability of the glass during the crystallization process. The lower limit of the P2O5 weight percentage content is preferably 1.8%; but if too much P2O5 is contained, it is easy to reduce the devitrification resistance of the glass and produce phase separation of the glass, and the mechanical properties of the glass tend to deteriorate. Therefore, the upper limit of the P2O5 content is 2.6%; in some embodiments, the glass composition may contain approximately 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, and 2.6% P2O5.
[0035] ZrO2 is a crystal nucleating agent and helps to improve the chemical stability of the glass. The lower limit of the ZrO2 content in the present application is 3.5%, but if too much ZrO2 is contained, the devitrification resistance of the glass is easily reduced, and the difficulty of controlling the glass crystallization process increases. Therefore, the upper limit of the ZrO2 content is 5.5%. In some embodiments, the glass composition may contain about 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5% ZrO2.
[0036] This embodiment optionally introduces 0-1% K2O by mass into the glass composition, such as 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% K2O. When there are multiple alkali metal oxides in the glass composition, the mixed alkali effect can be exerted in the chemical strengthening process of the microcrystalline glass, which helps to improve the chemical stability of the glass. The interaction of multiple alkali metal oxides can improve the low-temperature melting and formability of the glass, and reduce the difficulty of chemical strengthening of the microcrystalline glass. Preferably, the content of K2O is 0.5-1%.
[0037] In this embodiment, Y2O3 with a mass percentage of 0 to 0.5% is optionally introduced into the glass composition, such as 0%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%. The appropriate amount of Y2O3 can improve the density of the glass phase and the overall strength of the microcrystalline glass. If the content of Y2O3 is too high, it will be difficult to obtain a large compressive stress value during the chemical strengthening treatment of the microcrystalline glass. Preferably, the content of Y2O3 is 0.2 to 0.5%.
[0038] The glass composition of this embodiment may further include a clarifier, which includes one or more components of Sb2O3 and SnO2, and the lower limit of the mass percentage of the clarifier is 0% and the upper limit is 0.4%. In some embodiments, the glass composition may include about 0%, 0.1%, 0.2%, 0.3%, 0.4% of the clarifier. Preferably, the content of the clarifier is 0.2-0.4%.
[0039] In an optional implementation of this embodiment, Li2O / (SiO2+Al2O3): 0.1-0.2. The ratio of the total content of Li2O to SiO2 and Al2O3 in the glass composition of this embodiment can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%. It should be noted that based on the proportional relationship of the component contents, the formation of lithium silicate, lithium disilicate, and petalite crystal phases in the microcrystalline glass can be effectively achieved.
[0040] In the optional implementation of this embodiment, the crystallinity of the glass-ceramic is 58-75%. It is worth mentioning that the crystal phase has a higher melting point than the glass phase. If the glass-ceramic contains too much crystal and too little glass phase, the softening point temperature of the glass-ceramic will be increased, which is not conducive to the post-processing of the thermal processing (such as hot bending) of the glass-ceramic; in addition, if the crystal phase is too high in order to improve the strength of the glass, it will also be unfavorable for the post-processing of cold processing (such as grinding, cutting, etc.) due to the excessive hardness of the glass. Based on this, on the basis of the optimized glass formula system and oxide content provided in the embodiment of the present application, the crystallinity of the glass-ceramic is controlled below 75%, and a glass-ceramic with a softening point temperature less than or equal to 720°C can be obtained within the provided crystallinity range, so the temperature required for subsequent thermal processing can be reduced. In addition, the glass-ceramic based on this crystallinity range will not make the strength of the glass-ceramic too high while ensuring a certain strength, and the difficulty of subsequent cold processing is also reduced and the processing quality is improved.
[0041] It is also worth mentioning that the microcrystalline glass of the embodiment of the present application meets at least one of the following indicators: glass transition temperature less than or equal to 650°C, glass softening temperature less than or equal to 720°C, Vickers hardness less than or equal to 710kgf / mm 2 , the average crystal particle size is less than or equal to 30nm, the average transmittance relative to the visible light with a wavelength of 380-780nm is greater than or equal to 80% when the thickness is 0.6mm, the |B| value (the absolute value of the yellow-blue value of the 0.6mm microcrystalline glass) is 0.6-1 when the thickness is 0.6mm, and the haze is 0.15-0.25% when the thickness is 0.6mm. It can be seen that the microcrystalline glass of the embodiment of the present application can have a lower softening temperature and a suitable crystal size while achieving relatively excellent mechanical properties. The lower softening temperature makes subsequent deep processing easier, and the suitable crystal size ensures the optical performance.
[0042] Next, an embodiment of the present application further provides a deep-processed microcrystalline glass product, which is obtained by subjecting the microcrystalline glass provided by any implementation method in the aforementioned embodiments to heat processing and cold processing.
[0043] Correspondingly, an embodiment of the present application further provides a method for deep processing of microcrystalline glass, which specifically includes: sequentially performing preheating treatment, hot bending forming treatment and cooling treatment on the aforementioned microcrystalline glass to obtain a deep-processed microcrystalline glass product.
[0044] In practical applications, glass raw materials are first prepared according to the components and contents of the aforementioned microcrystalline glass, and the glass raw materials are evenly mixed and melted at 1580°C, and then clarified, homogenized, formed, and annealed to obtain the substrate glass; then, the plate glass is subjected to a nucleation treatment at 530-580°C for 2-5h, and then crystallized at 650-700°C for 0.5-1.5h, and cooled to room temperature to obtain microcrystalline glass; next, the microcrystalline glass is sequentially passed through four preheating stations, three hot pressing stations, and two cooling stations to finally obtain a deep-processed microcrystalline glass product.
[0045] The temperature of the preheat treatment is 550-770°C, the time is 70-400s, the temperature of the hot bending treatment is 620-770°C, the time is 80-300s, the pressure is 0.3-0.9MPa, and the temperature of the cold working treatment is 400-650°C, the time is 80-200s, and the pressure is 0.3MPa.
[0046] For the four preheating stations, the temperature of the first preheating station is 550-700°C and the working time is 90s, the temperature of the second preheating station is 650-735°C and the working time is 90s, the temperature of the third preheating station is 720-765°C and the working time is 70-90s, and the temperature of the fourth preheating station is 720-765°C and the working time is 70-90s; for the hot bending forming process, the temperature of the first hot pressing station is 720-765°C, the working time is 70-90s, and the pressure is 0 .3~0.6MPa, the temperature of the second hot pressing station is 700~765℃, the working time is 70~90s, and the pressure is 0.9MPa, the temperature of the third hot pressing station is 620~735℃, the working time is 70~90s, and the pressure is 0.9MPa; for the two cooling stations, the temperature of the first cooling station is 500~650℃, the working time is 90~100s, and the pressure is 0.3MPa, and the temperature of the second cooling station is 400~500℃, the working time is 90s, and the pressure is 0.3MPa. As shown in Table 1, this is an exemplary process parameter table of deep processing provided in this embodiment:
[0047] Table 1
[0048]
[0049]
[0050] It is worth mentioning that this embodiment also provides a method for chemically strengthening microcrystalline glass, including: placing the deep-processed microcrystalline glass product in a preheating furnace and preheating it at 380°C for 30 to 60 minutes, and then immersing the deep-processed microcrystalline glass product in a salt bath at 450 to 500°C for strengthening for 280 to 600 minutes to obtain chemically strengthened microcrystalline glass.
[0051] Chemical strengthening refers to placing the microcrystalline glass in a salt bath for ion exchange treatment, so that the microcrystalline glass forms a compressive stress layer and a tensile stress layer. The salt bath of this embodiment is a mixed salt bath, exemplarily including potassium nitrate and sodium nitrate. Of course, in some embodiments, it can further include lithium nitrate. Preferably, the mass fraction of potassium nitrate in the salt bath is 75%, and the mass fraction of sodium nitrate is 25%. Compared with traditional multiple strengthening, this embodiment can strengthen in a tempering furnace once to simultaneously complete multiple ion exchange behaviors between the salt bath and the glass, thereby improving the chemical strengthening efficiency and reducing the amount of salt bath used. After chemical strengthening treatment, the final chemically strengthened microcrystalline glass has a deeper compressive stress depth and a higher surface compressive stress.
[0052] In order to illustrate the technical effect of the microcrystalline glass of this embodiment, the present application has conducted tests on microcrystalline glasses of different components and contents to determine the characteristics of each glass product. Examples 1 to 11 in Table 1 show the components, contents, test conditions and test results of the microcrystalline glasses of various compositions of the present application. Comparative Examples 1 and 2 show the specific components, contents, test conditions and test results of several microcrystalline glasses provided in the prior art.
[0053] Table 1 Examples 1 to 11 and Comparative Examples 1 to 2
[0054]
[0055]
[0056]
[0057] On the one hand, according to the comparison of the experimental data before and after the deep processing of Examples 1 to 11 in the above Table 1, it can be seen that after the deep processing, the content of the lithium disilicate crystal phase in the microcrystalline glass of the embodiment of the present application is higher than that before the deep processing, that is, the lithium silicate crystal phase will be further converted into the lithium disilicate crystal phase during the thermal processing.
[0058] On the other hand, according to the comparison of the test data before deep processing of Examples 1 to 11 and Comparative Examples 1 to 2 in Table 1 above, it can be seen that before deep processing, the embodiments of the present application control the crystallinity of the microcrystalline glass within the range of 58-75% by adopting a crystallization temperature lower than that of Comparative Examples 1 to 2, and the glass softening temperature is correspondingly controlled within the temperature range below 720°C, which is significantly lower than that of Comparative Examples 1 to 2, so hot bending can be performed using a relatively low heat processing temperature. In addition, although the mechanical properties of the microcrystalline glass of the embodiments of the present application are lower than those of Comparative Examples 1 to 2 before deep processing, the difficulty of cold processing can be reduced. Of course, with the subsequent heat processing, the microcrystalline glass will further crystallize. It can be seen that the crystallinity of the microcrystalline glass of the embodiments of the present application is greatly improved compared to before deep processing, and relatively excellent mechanical properties can still be obtained in the end.
[0059] On the other hand, based on the formulation system of the embodiments of the present application and the control of crystallinity before deep processing, the optical properties (|B| value, haze and transmittance) of the microcrystalline glass are better than those of comparative examples 1 to 2 before and after deep processing.
[0060] Finally, according to the comparison of the experimental data before and after deep processing of Examples 1 to 11 and Comparative Examples 1 to 2 in Table 1 above, it can be seen that the change of the average crystal particle size of the microcrystalline glass in the embodiments of the present application before and after deep processing is controllable, while the average crystal particle size of the microcrystalline glass in Comparative Examples 1 to 2 after deep processing increases significantly after deep processing, resulting in the degradation of the optical properties of the deep-processed microcrystalline glass products.
[0061] Furthermore, mechanical property tests were conducted on glass-ceramics of different formulations with a crystallinity of 58-75% in this embodiment. The glass-ceramics of different formulations provided in this embodiment have different residual glass phase compositions. The specific test results are shown in Table 2:
[0062] Table 2
[0063]
[0064] Based on the test results in the above table, it can be seen that the embodiment of the present application preferably controls the crystallinity of the microcrystalline glass to 58-75%, so that the glass phase can form good crystal properties in the microcrystalline glass while the residual glass phase can also have good properties, fully ensuring the elastic modulus, strength and other mechanical properties of the microcrystalline glass.
[0065] Based on the above scheme of the present application, the crystalline phase of the microcrystalline glass includes petalite, lithium disilicate and lithium silicate, and the crystallinity is less than or equal to 75%; the content of petalite accounts for 30-60% of the total crystal content, the content of lithium disilicate accounts for 16-38% of the total crystal content, the content of lithium silicate accounts for 10-35% of the total crystal content, and the total content of petalite and lithium disilicate accounts for more than 65% of the total crystal content. Through the implementation of this application, the strength of the microcrystalline glass can be guaranteed within the set crystallinity range while effectively reducing the glass softening temperature, so that the difficulty of subsequent deep processing is reduced. In addition, in the subsequent deep processing process, the lithium silicate of the microcrystalline glass can continue to react and be converted into lithium disilicate, which can effectively control the total crystal content and crystal size.
[0066] It is also worth mentioning that due to the above-mentioned performance advantages of the microcrystalline glass and deep-processed microcrystalline glass products provided in the embodiments of the present application, they can be widely used in the production of glass protective cover plates for electronic devices, glass components or windows for household appliances, etc.
[0067] Finally, it should be noted that in the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0068] The above is a description of the microcrystalline glass, glass products and deep processing methods suitable for deep processing provided by the present application. For those skilled in the art, based on the ideas of the embodiments of the present application, equivalent substitutions made in specific implementation methods and application scopes should all be included in the scope of the claims of the present application. In summary, the content of this specification should not be understood as a limitation on the scheme of the present application.
Claims
1. A glass-ceramic suitable for deep processing, characterized in that: The crystalline phases of the microcrystalline glass include petalite, lithium disilicate and lithium silicate, and the degree of crystallinity is less than or equal to 75%; the content of the petalite accounts for 30-60% of the total crystal content, the content of the lithium disilicate accounts for 16-38% of the total crystal content, the content of the lithium silicate accounts for 10-35% of the total crystal content, and the total content of the petalite and the lithium disilicate accounts for more than 65% of the total crystal content.
2. The glass-ceramic according to claim 1, characterized in that: The crystal phase of the microcrystalline glass also includes at least one of lithium phosphate and β-spodumene.
3. The glass-ceramic according to claim 1, characterized in that: The crystallinity of the microcrystalline glass is 58-75%.
4. The glass-ceramic according to claim 1, characterized in that: The content of petalite accounts for 40-60% of the total crystal content, and / or the content of lithium disilicate accounts for 16-30% of the total crystal content, and / or the content of lithium silicate accounts for 15-35% of the total crystal content.
5. The glass-ceramic according to claim 1, characterized in that: Its components, measured by weight percentage, include: SiO2: 70-75%, B2O3: 0.35-1.2%, Al2O3: 7.5-9.5%, Na2O: 0.5-1.5%, Li2O: 9.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
6. The glass-ceramic according to claim 5, characterized in that: Its components, measured by weight percentage, include: SiO2: 70-72%, B2O3: 0.5-1.2%, Al2O3: 8-9.5%, Na2O: 1-1.5%, Li2O: 10.5-12%, P2O5: 1.8-2.6%, and ZrO2: 3.5-5.5%.
7. The glass-ceramic according to claim 5, characterized in that: Its components, in terms of weight percentage, meet the following conditions: Li2O / (SiO2+Al2O3): 0.1-0.
2.
8. The glass-ceramic according to claim 5, characterized in that: The components thereof, in terms of weight percentage, further include: K2O: 0-1%, Y2O3: 0-0.5%, and clarifier: 0-0.4%.
9. The glass-ceramic according to claim 8, characterized in that: The components thereof, in terms of weight percentage, further include: K2O: 0.5-1%, Y2O3: 0.2-0.5%, and clarifier: 0.2-0.4%.
10. The glass-ceramic according to claim 9, characterized in that: The crystallization temperature is 655-700°C.
11. The glass-ceramic according to any one of claims 1 to 10, characterized in that: Meet at least one of the following indicators: glass transition temperature less than or equal to 650°C, glass softening temperature less than or equal to 720°C, Vickers hardness less than or equal to 710kgf / mm 2 , the average crystal particle size is less than or equal to 30nm, the average transmittance of visible light with a wavelength of 380 to 780nm is greater than or equal to 80% when the thickness is 0.6mm, the |B| value when the thickness is 0.6mm is 0.6 to 1, and the haze when the thickness is 0.6mm is 0.15 to 0.25%.
12. A deep-processed glass-ceramic product, characterized in that: The microcrystalline glass is obtained by subjecting the microcrystalline glass as described in any one of claims 1 to 11 to heat treatment and cold treatment.
13. A deep processing method of glass-ceramics according to any one of claims 1 to 11, characterized in that: include: The microcrystalline glass is subjected to preheating treatment, hot bending forming treatment and cooling treatment in sequence to obtain a deep-processed microcrystalline glass product.
14. The deep processing method according to claim 13, characterized in that: The preheating treatment is performed at a temperature of 550 to 770°C for 70 to 400 seconds, the hot bending treatment is performed at a temperature of 620 to 770°C for 80 to 300 seconds, and the pressure is 0.3 to 0.9 MPa, and the cold working treatment is performed at a temperature of 400 to 650°C for 80 to 200 seconds, and the pressure is 0.3 MPa.
15. The deep processing method according to claim 13, characterized in that: The preheating treatment needs to go through four preheating stations, the temperature of the first preheating station is 550-700°C, the working time is 90s, the temperature of the second preheating station is 650-735°C, the working time is 90s, the temperature of the third preheating station is 720-765°C, the working time is 70-90s, and the temperature of the fourth preheating station is 720-765°C, the working time is 70-90s; the hot bending forming treatment needs to go through three hot pressing stations, the temperature of the first hot pressing station is 720-765°C, the working time is 70-90s, and the pressure is 0 .3~0.6MPa, the temperature of the second hot pressing station is 700~765℃, the working time is 70~90s, and the pressure is 0.9MPa, the temperature of the third hot pressing station is 620~735℃, the working time is 70~90s, and the pressure is 0.9MPa; the cooling treatment needs to go through two cooling stations, the temperature of the first cooling station is 500~650℃, the working time is 90~100s, and the pressure is 0.3MPa, the temperature of the second cooling station is 400~500℃, the working time is 90s, and the pressure is 0.3MPa.